2023
DOI: 10.1038/s41467-023-37146-z
|View full text |Cite
|
Sign up to set email alerts
|

Executioner caspases restrict mitochondrial RNA-driven Type I IFN induction during chemotherapy-induced apoptosis

Abstract: During apoptosis, mitochondrial outer membrane permeabilization (MOMP) enables certain mitochondrial matrix macromolecules to escape into the cytosol. However, the fate of mitochondrial RNA (mtRNA) during apoptosis is unknown. Here, we demonstrate that MOMP results in the cytoplasmic release of mtRNA and that executioner caspases-3 and -7 (casp3/7) prevent cytoplasmic mtRNA from triggering inflammatory signaling. In the setting of genetic or pharmacological casp3/7 inhibition, apoptotic insults result in mtRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…NPs are known to influence immune responses in diverse organisms, and this is particularly relevant for clams, which primarily rely on innate, nonlymphoid immune functions such as phagocytosis to mitigate stress. , This aspect was confirmed by both GO and KEGG analyses (Data Set S3). DEGs, as evident in the presented data, were chiefly engaged in processes like protein digestion and autophagy, with those related to mitochondrial functionsuch as ATP generation and mitochondrial respiratory chainbeing significantly enriched in the p-NP group (Figure d,e), highlighting a connection to mitochondrial and associated complications like energy production anomalies and cell death. , …”
Section: Resultsmentioning
confidence: 62%
See 4 more Smart Citations
“…NPs are known to influence immune responses in diverse organisms, and this is particularly relevant for clams, which primarily rely on innate, nonlymphoid immune functions such as phagocytosis to mitigate stress. , This aspect was confirmed by both GO and KEGG analyses (Data Set S3). DEGs, as evident in the presented data, were chiefly engaged in processes like protein digestion and autophagy, with those related to mitochondrial functionsuch as ATP generation and mitochondrial respiratory chainbeing significantly enriched in the p-NP group (Figure d,e), highlighting a connection to mitochondrial and associated complications like energy production anomalies and cell death. , …”
Section: Resultsmentioning
confidence: 62%
“…Notably, clams exposed to p-NPs showed heightened apoptosis. , Similarly, high-dose n-NPs also induced apoptosis, albeit to a lesser extent compared with p-NP exposure. The mitochondrial route, often activated under stress conditions, is a primary initiator of apoptosis. ,, The study found that p-NPs intensified ROS production in R. philippinarum, activating this mitochondrial route.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations